Studi Pengaruh Kecepatan Potong Dan Kedalaman Pemotongan Terhadap Kekasaran Permukaan Benda Hasil Pembubutan Menggunakan Pahat HSS Terhadap Material St41 - Wawanto, Rendi; -, Erwansyah; -, Ariyanto (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2021)
In the machining process is very need high precision to get a good result. One of the benchmarks of the quality of the surface of the product workmanship in the machining process is surface roughness. The research was aimed at determining the contribution of the parameters of the machining process conducted on lathes. The research was conducted using lathes with machining process parameters that vary from cutting speed, and depth of nutrition, as well as using fixed parameters of feeding. The experiment was conducted using experimental method with the amount of cutting speed value (Vc) used by St 41 material of 20-25 m/min. The values used in this study were limited to 20, 21, and 22 m/min (Vc) values and cutting depths of 0.5, 0.8, and 1.0 mm. Research shows the results of turning (Vc) 20 m / min. best depth using a cutting depth of 0.5 mm with a surface roughness value (Ra) of 2,743 μm, and (Vc) of 21 m/min, the best depth using a depth of 0.5 mm with a surface roughness value (Ra)1,495 μm, and using (Vc) 22 m/min, the best depth uses a depth of 0.8 mm with a surface roughness value (Ra)1,376 μm. the best value of the turning process uses 3 cutting speeds and 3 cutting depths at the turning process using (Vc) 22 m/min with a depth of 0.8 mm with a surface roughness value (Ra)1,376 μm